Optimal Sizing of Stand-alone PV System using Artificial Bee Colony Algorithm - Md. Yusri; Khalil, Ashraf; Ang , Swee Peng (International Journal of Integrated Engineering, 2021)
The alarming rate of depletion of fossil fuels due to the increasing energy demands has increased the reliance on renewable energy. Renewable resources, such as solar and wind, are excellent alternatives to fossil fuels due to their sustainability and they do not produce harmful gases to the environment. The most promising renewable energy resource is the solar energy since it is available almost everywhere. Renewable energy systems have considerable high initial cost. In order to reduce the cost, the size of the system should be optimized. Optimization means increasing the output energy while reducing the cost. Recently intelligent optimization techniques have been used to solve complex engineering problems. Artificial Bee Colony (ABC) is one of these techniques. In this paper we present a sizing and optimization technique for renewable energy systems using ABC algorithm. The model for the PV panel, the battery, and the loads are used to optimize the system. The method is applied to optimize a typical system and the results of the design are optimum as proved by simulation and comparison with the results of the published methods.